2021
DOI: 10.1136/jitc-2020-001636
|View full text |Cite
|
Sign up to set email alerts
|

Combination of vasculature targeting, hypofractionated radiotherapy, and immune checkpoint inhibitor elicits potent antitumor immune response and blocks tumor progression

Abstract: BackgroundTumor endothelial marker 1 (TEM1) is a protein expressed in the tumor-associated endothelium and/or stroma of various types of cancer. We previously demonstrated that immunization with a plasmid-DNA vaccine targeting TEM1 reduced tumor progression in three murine cancer models. Radiation therapy (RT) is an established cancer modality used in more than 50% of patients with solid tumors. RT can induce tumor-associated vasculature injury, triggering immunogenic cell death and inhibition of the irradiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 71 publications
2
16
0
Order By: Relevance
“…Meanwhile, hypoxia also supports the differentiation and function of MDSCs and Tregs via various immunosuppressive molecules to mediate antitumor immune escape [261]. Combination of vasculature targeting and immune checkpoint inhibitor was demonstrate to elicit potent antitumor response in preclinical study, which endow the further application of inhibiting vasculature plus immunotherapy high promise [262].…”
Section: Cancer-associated Vasculature and The Immune Systemmentioning
confidence: 99%
“…Meanwhile, hypoxia also supports the differentiation and function of MDSCs and Tregs via various immunosuppressive molecules to mediate antitumor immune escape [261]. Combination of vasculature targeting and immune checkpoint inhibitor was demonstrate to elicit potent antitumor response in preclinical study, which endow the further application of inhibiting vasculature plus immunotherapy high promise [262].…”
Section: Cancer-associated Vasculature and The Immune Systemmentioning
confidence: 99%
“…Thus, the combination of HFRT and ICIs to enhance the radiotherapy-induced antitumor T-cell response comprises a viable modality. This approach has been applied to numerous tumor types with satisfactory results, particularly lung cancer (23)(24)(25). Shaverdian et al (23) reported that patients with advanced lung cancer who had undergone radiotherapy prior to immunotherapy manifested longer progression-free survival (4.4 vs. 2.1 months) and overall survival (10.7 vs.…”
Section: Discussionmentioning
confidence: 99%
“…Both combination and monotherapies used to enhance specific immune facets within the TME have shown potential to enable cytotoxic effects of vaccines in preclinical studies. Strategies, such as directly targeting TME vasculature (angiogenesis), targeting CAFs, and persistent cytokines, such as GM-CSF, IDO1, BAFF and other interleukins, with cancer vaccines have shown relatively consistent antitumoral effectiveness in preclinical models [ 222 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. DNA vaccines utilizing novel nanobiomaterials include minimally invasive, injectable smart hydrogels [ 230 ].…”
Section: Basic Research In Cancer Immunologymentioning
confidence: 99%